Exploring the Influence of AI-Driven SC Efficiency on Customer Experience in Retail: A Data-Driven Approach to Enhancing Front-End Operations - Mohammed Alenazi (International Journal of Intelligent Systems and Applications in Engineering, 2026)
Improvement of customer experiences is the prime agenda of today’s competitive retailing, and the efficiency of the backend supply chain (SC) plays a very important role in helping to reach this goal. The present research study at the backend SC processes and their interlink with the front-end customer satisfaction of the retail sector, with special emphasis on the integration of technologies driven by AI. This research estimates the contribution of AI-powered tools, like predictive analytics, automated inventory management, and logistics optimization, to the enhancement of operational efficiency and into customer experience, through data. The chief objective is to demonstrate the beneficiary of AI tools to elevate operational efficiency and consumer satisfaction. Through evaluating key performance metrics composed of product availability, speed of order fulfillment, and service quality, this research study will show both direct as well as indirect ways streamlined backend operations that shape customer satisfaction and loyalty. The current study uses mixed methods that combine both quantitative as well as qualitative approaches. The quantitative data gathered from 114 retailers through structured questionnaires is examined by the SPSS software tool. The analysis was performed using SPSS version 27, applying statistical methods such as correlation, ANOVA, and regression. The qualitative data was collected from 15 experienced retailers and evaluated through thematic analysis. The findings also forecast the criticality of backend efficiencies in delivering seamless and responsive front-end customer experience. The present research provides actionable insight for retailers desirous of optimizing AI adoption in SC management with a view to engendering long-term customer loyalty and competitive advantage.